Legal Implications For Victims Of Telegram Fraud In The Jurisdiction Of The South Sumatra Polda - Marlin, Marlin; Mahfuz, Abdul Latif (Universitas Muhammadiyah Sumatera Utara, 2024)
Digital fraud is the most common cybercrime and is a global problem. Cases of fraud committed by online media using Telegram accounts are increasing from year to year. The problem in this investigation is the legal implications for victims of criminal acts of wire fraud in the jurisdiction of the South Sumatra Regional Police. The research method used is a standard legal research method that uses secondary data resulting from library research. A study of the legal implications for legal protection for victims of wire fraud in the jurisdiction of the South Sumatra Regional Police shows that although the victims' rights have been fulfilled, the victims have not received complete justice. Victims are in a vulnerable position in providing legal protection by reporting a criminal incident, explaining who the perpetrator of the crime is, and/or providing evidence, both physical and non-evidence. Physical suffering and material and non-physical losses - material losses for law enforcement officers